Mechanism of Orientation-Dependent Asymmetric Charge Transport in Tunneling Junctions Comprising Photosystem I - Castañeda Ocampo, Olga E. (J Am Chem Soc, 2015)
[Image: see text] Recently, photoactive proteins have gained a lot of attention due to their incorporation into bioinspired (photo)electrochemical and solar cells. This paper describes the measurement of the asymmetry of current transport of self-assembled monolayers (SAMs) of the entire photosystem I (PSI) protein complex (not the isolated reaction center, RCI), on two different “director SAMs” supported by ultraflat Au substrates. The director SAMs induce the preferential orientation of PSI, which manifest as asymmetry in tunneling charge-transport. We measured the oriented SAMs of PSI using eutectic Ga–In (EGaIn), a large-area technique, and conducting probe atomic force microscopy (CP-AFM), a single-complex technique, and determined that the transport properties are comparable. By varying the temperatures at which the measurements were performed, we found that there is no measurable dependence of the current on temperature from ±0.1 to ±1.0 V bias, and thus, we suggest tunneling as the mechanism for transport; there are no thermally activated (e.g., hopping) processes. Therefore, it is likely that relaxation in the electron transport chain is not responsible for the asymmetry in the conductance of SAMs of PSI complexes in these junctions, which we ascribe instead to the presence of a large, net dipole moment present in PSI.